Evaluasi Implementasi Peraturan LKPP No 7/2021 tentang SDM PBJ di Kabupaten Ogan Ilir - Helisa Nova, Deta; M. Sobri, Kgs.; Nadjib, Abdul (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2024)
Abstract PBJ is a key element in the growth strategy and public service delivery of the Indonesian government. However, challenges such as complex bureaucracy, corruption risks, and lack of transparency still need to be addressed. The 2023 KPK Integrity Assessment Survey (SPI) results indicate that Ogan Ilir Regency remains vulnerable to irregularities. E-procurement is considered a potential solution, but its implementation requires fundamental changes in administrative processes and HR management. Therefore, this study evaluates the implementation of LKPP Regulation No. 7/2021 on PBJ HR in Ogan Ilir Regency using the OECD evaluation framework: Input, Process, Output, Intermediate Outcome, and Strategic Outcome. This study employs a qualitative descriptive approach with primary and secondary data sources. The results show that the implementation of LKPP Regulation 7/2021 in Ogan Ilir Regency has yielded positive results in some aspects, such udget allocation and the facilitation of education and training, but significant challenges remain in meeting the needs for competent HR. Some obstacles include the perception of high legal risks, lack of interest from civil servants in transitioning to JF PPBJ roles, and regulatory conflicts. Although there has been an improvement in PBJ performance in Ogan Ilir Regency, stakeholder assessments of PBJ management quality still show unsatisfactory results. Therefore, intensive efforts are needed to enhance the alignment between competency requirements and practical implementation, strengthen interest among civil servants in PBJ management roles, and increase awareness of the procedures for becoming JF PPBJ. This will help achieve more professional and integrity-driven PBJ HR. Keywords: Human Resources Management, LKPP Regulation 7/2021, Policy Evaluation